Mercury cadmium telluride : A superior choice for near room temperature infrared detectors (Review Paper) - Ashokan, R.; Sivananthan, S.; Velicu, S. (Defence Science Journal, 2002)
"The advantages of mercury cadmium telluride (HgCdTe) for hot IR detector applications are discussed. Molecular beam epitaxy (MBE) is used to grow advanced device structures for this purpose. MBE offers the potential to grow HgCdTe heterostructure layers on large [7.62 cm (3 in.) or more] silicon substrates leading to very large format and high performance IR focal plane arrays in the future. Preliminary material and device properties achieved in p+-v-n+ device structures grown on 7.62 cm (3 in.) (211 )-oriented silicon wafers are discussed.